2019
DOI: 10.1021/acschemneuro.9b00368
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel δ Opioid Receptor Inverse Agonists without a Basic Nitrogen Atom and Their Antitussive Effects in Mice

Abstract: Our previous results showed that naltrindole (NTI) derivatives with certain types of electron-withdrawing groups as an N-substituent showed δ opioid receptor (DOR) inverse agonistic activities. We therefore synthesized N-acylated NTI derivatives 3a–e and observed that N-benzoyl and N-cyclopropanecarbonyl derivatives SYK-736 (3b) and SYK-623 (3c) were DOR full inverse agonists and the N-acryloyl derivative 3d was a DOR partial inverse agonist. SKY-623 was over 110-fold more potent than the reference compound IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Compound 7 [ 24 , 25 ], which is the key intermediate for the synthesis of the target sulfonamide-type NTI derivatives, was synthesized from naltrexone hydrochloride ( 1 ) ( Scheme 1 ). Fischer indolization of 1 with phenylhydrazine hydrochloride gave NTI ( 2 ) [ 27 , 28 ] in 99% yield, which was treated with acetic anhydride to afford diacetate 3 in 95% yield.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Compound 7 [ 24 , 25 ], which is the key intermediate for the synthesis of the target sulfonamide-type NTI derivatives, was synthesized from naltrexone hydrochloride ( 1 ) ( Scheme 1 ). Fischer indolization of 1 with phenylhydrazine hydrochloride gave NTI ( 2 ) [ 27 , 28 ] in 99% yield, which was treated with acetic anhydride to afford diacetate 3 in 95% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, compounds 9f and 9g showing high efficacies were almost full inverse agonists. The activity of 9f was comparable to that to SYK-623 (EC 50 = 0.969 nM, E max = −91.2%) [ 25 ]. Interestingly, both compounds possessing the cyclopropyl moiety together with either a C=O or a S=O functionality were inverse agonists, while the NTI-bearing cyclopropylmethyl group, with neither the C=O nor S=O moiety, was a neutral antagonist.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are many studies in the literature on central opioid peptide antagonism and exhausting exercise no other studies have been found on how central antagonism affects glycogen levels in peripheral tissues after exhausting exercise. On the other hand, since NX and NT are also inverse agonists [43,44], the basal activity of endogenous OPR has decreased, thus allowing us to see the effects of OPR on glycogen levels more clearly. However, in order to explain the existing and possible mechanisms in more detail, further studies are needed.…”
Section: Discussionmentioning
confidence: 99%